Osmotic Dehydration of Banana Slices Using Direct and Indirect Sonication: Optimization and Microstructure Analysis. Issue 1 (28th December 2015) - Farhaninejad, Zeynab; Fathi, Milad; Shahedi, Mohammad; Sadeghi, Morteza
Abstract: The objective of this work was to study osmotic dehydration of banana slices using direct and indirect sonication. The optimum process was determined by response surface methodology and the effect of treatments, including mechanical agitation, indirect sonication and direct sonication, on banana microstructure was analyzed by scanning electron microscopy. Optimization of process in terms of maximum water loss and minimum solid gain, color and surface area changes was performed, and the direct sonication in sucrose concentration of 53.95% (w/v) had the best performance. Microstructure studies proved that ultrasound was responsible for creation of microchannels through the cell distortion and disconnection between cavities. Moreover, effective diffusivity for solid and water diffusion increased by 1, 342.1% and 1, 184.5% for direct sonication and 229.0% and 294.7% for indirect sonication for sucrose concentration 60% (w/v), respectively. Ultrasound led to increase of porosity by about 21.38% and 36.47% for indirect and direct sonication, respectively, in comparison with untreated sample. Practical Applications: Drying is an expensive and energy intensive process needing long‐time operation. Indirect ultrasound‐assisted osmotic dehydration was previously used to enhance drying efficiency. In this article, direct ultrasound was applied to dehydrate banana slices. The results indicated that this method is very powerful, which could increase effective diffusion up to 1, 342.1%. Response surface methodology was applied to maximize water loss and minimize solid gain, color and surface area changes. Direct sonication could be recommended for dehydration of fruits and vegetables.